2009
DOI: 10.1007/s12088-009-0024-y
|View full text |Cite
|
Sign up to set email alerts
|

Growth promotion of wheat seedlings by Exiguobacterium acetylicum 1P (MTCC 8707) a cold tolerant bacterial strain from the Uttarakhand Himalayas

Abstract: Exiguobacterium acetylicum strain 1P (MTCC 8707) is a gram-positive, rod-shaped, yellow pigmented bacterium isolated from soil on nutrient agar plates at 4°C. The identity of the bacterium was arrived on the basis of the biochemical characterization, BIOLOG sugar utilization pattern and sequencing of the 16S rRNA gene. It grew at temperatures ranging from 4 to 42°C, with temperature optima at 30°C. It expressed multiple plant growth promotion attributes such as phosphate solubilization, indole acetic acid (IAA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(34 citation statements)
references
References 30 publications
0
32
1
1
Order By: Relevance
“…Important contributing feature of NII-0906 was the increased P-solubilization, which was four times higher than that of any other Exiguobacterium species. Selvakumar et al (2008) reported 22.6 ± 2.16 µg/mL per day of P-solubilization at 30…”
Section: Discussionmentioning
confidence: 99%
“…Important contributing feature of NII-0906 was the increased P-solubilization, which was four times higher than that of any other Exiguobacterium species. Selvakumar et al (2008) reported 22.6 ± 2.16 µg/mL per day of P-solubilization at 30…”
Section: Discussionmentioning
confidence: 99%
“…Further it is also been reported to increase the growth and nutrient uptake of wheat seedlings under glass house conditions (Selvakumar et al, 2010). Phosphate solubilizing Exiguobacterium strains were isolated from acidic soils of Argentina (Collavino et al, 2010) and paddy fields of Eastern Uttar Pradesh in India (Kumar et al, 2010).…”
Section: Exiguobacteriummentioning
confidence: 99%
“…Several bacteria support plant growth indirectly, via production of antagonistic substances or by inducing resistance against plant pathogens (7,10,11). By producing plant growth regulators, these organisms are reported to influence seed germination and seedling growth (7).…”
mentioning
confidence: 99%